Oxygen electrode degradation in solid oxide cells operating in electrolysis and fuel cell modes: LSCF destabilization and interdiffusion at the electrode/electrolyte interface. (8th September 2021) - Monaco, F.; Ferreira-Sanchez, D.; Hubert, M.; Morel, B.; Montinaro, D.; Grolimund, D.; Laurencin, J.
Abstract: Three long-term experiments have been performed in SOEC and SOFC modes at different operating temperatures. The durability tests confirm a higher degradation in electrolysis mode with respect to fuel cell operation. In addition, a larger increase of the ohmic resistance is observed for the cell operated at higher temperature in electrolysis mode. The oxygen electrodes of the pristine and tested cells have been characterized by synchrotron X-ray micro-diffraction and micro-fluorescence to assess the relation between the material destabilization and the formation of insulating phases due to interlayer diffusion. The analyses of the pristine cell confirm the presence after the electrode sintering of strontium zirconate and a Gd-rich interdiffusional layer in the electrolyte just below the zirconates. Moreover, evolutions in the LSCF unit cell volume reveal strontium segregation after aging. The associated material destabilization is linked to the accumulation of SrZrO3 at the barrier layer/interdiffusional layer interface in operation and both phenomena are found to be thermally-activated and promoted in electrolysis mode. Finally, the crystallographic evolution of the interdiffusional layer in electrolysis mode has been investigated by X-ray diffraction. A slight increase of the phase peaks intensity detected at the highest temperature is correlated to the largest formation of SrZrO3 observed in this condition. Based on these preliminary results, it is proposed that the loss of Zr 4+ from the electrolyte due to the zirconates formation could facilitate the interdiffusion of Gd, reducing the local ionic conductivity and thus significantly contributing to the largest increase in the ohmic resistance observed in this case. Graphical abstract: Image 1 Highlights: Long-term tests in SOFC and SOEC modes at different operating temperatures. Oxygen electrode/electrolyte interface characterized by synchrotron-based μXRD/μXRF. Strontium zirconates and a Gd-rich interdiffusional layer detected after sintering. Evolution of the LSCF unit cell volume reveals Sr segregation in SOEC operation. Possible evolution of the interdiffusional layer in SOEC mode at high temperature.